Vitamin D Receptor Polymorphism and Myasthenia Gravis in Chinese Han Population - Han, Ji-Lan; Yue, Yao-Xian; Gao, Xiang; Xie, Yan-Chen; Hao, Hong-Jun; Li, Hong-Yan; Yu, Xiao-Long; Li, Jie; Duan, Rui-Sheng; Li, Hai-Feng (Frontiers in Neurology, 2021)
Myasthenia gravis is an autoimmune disease in which antibodies bind to acetylcholine receptors or other functional molecules in the postsynaptic membrane at the neuromuscular junction. The immune regulating effect of vitamin D (VD) is one of its pluripotent effects apart from bone metabolism. The immunomodulatory actions of 1,25(OH)2D3 are mediated by its binding to VDR. In the study, we undertook a case–control study to explore the association between VDR gene polymorphism and the susceptibility and severity of MG patients. A Chinese cohort of 480 MG patients and 487 healthy controls was recruited, polymorphisms of VDR gene were determined with improved multiplex ligation detection reaction (iMLDR) technique and SNPscanTM technique. MG patients were classified into subgroups by essential clinical features and by a comprehensive classification. The frequencies of alleles and genotypes were compared between MG group and the control group, between each MG subgroup and the control group, and between each pair of MG subgroups. There were no significant differences in frequencies of alleles and genotypes between MG patients and healthy controls, between MG subgroups and healthy controls, and between each pair of MG subgroups in the analysis of subgroups classified by essential clinical features (onset age, gender, thymoma, AChRAb positivity, onset involvement) and the maximal severity (Oosterhuis score). In the analysis of subgroups with a comprehensive classification, the frequencies of alleles and genotypes in rs731236 showed significant differences between adult non-thymoma AChRAb negative MG subgroup and the control group, as well as the adult non-thymoma AChRAb positive MG group. In Chinese Han population, rs731236 was found to be possibly associated with adult non-thymoma AChRAb negative MG, which needs further confirmation.